Evaluating antimicrobial resistance in dairy farming: understanding real world interactions within the wastewater slurry environment - Lanyon, Christopher W. (2021)
Agriculture is a known source of environmental antimicrobial resistance (AMR). However, the ecological and human-health impact of antibiotic use and the related AMR in animal husbandry is poorly understood. One possible vector of AMR from agriculture to the environment is dairy slurry. Slurry stores are repositories of bovine faeces and urine, as well as waste milk, used footbath contents, parlour washings and other farm wastewater. As antibiotics, bacteria and antimicrobial resistance genes are present in bovine excreta and waste milk, and footbaths and farm wastewater may contain copper, zinc, formalin and other biocides, this creates an environment in which selective pressure may cause the proliferation and spread of AMR. Dairy slurry is often spread on arable and crop lands, potentially acting as a source of AMR into the environment, but also into the human and bovine food chains.